"I Think It's a Shame They are Calling Us a Ghetto, I Don't Think This a Ghetto." – Ambivalent Enactments of Living in Underprivileged Neighbourhoods. Issue 1 (1st January 2023) - Rosenlund Hansen, Stine; Weinreich Hansen, Mette
ABSTRACT: People and places are entangled through material, social, discursive and emotional relations, which makes it complex to understand the daily living in a certain place. In this article, we explore such entanglements, with an outset in two underprivileged neighbourhoods in Denmark, by drawing on two sets of theoretical thinking: The framework of multiplicity, and the concept of place. We argue that the neighbourhoods cannot be defined as either good or bad places of living. Rather they exist in complex ways, where what makes some people feel at home, is what makes others feel insecure, and where such ambivalent feelings can co-exist inherently for individual residents. Furthermore, our analysis shows that manifold enactments of residents and places enable multiple trajectories of how to live and identify oneself in relation to the neighbourhood.